2021
DOI: 10.1042/cs20201500
|View full text |Cite
|
Sign up to set email alerts
|

EB2 promotes hepatocellular carcinoma proliferation and metastasis via MAPK/ERK pathway by modulating microtubule dynamics

Abstract: Metastasis is the main cause of poor postoperative survival of hepatocellular carcinoma (HCC) patients. Cytoskeleton rearrangement is a key event in cancer metastasis. However, the significance of microtubule (MT), one of the core components of cytoskeleton, in this process is only beginning to be revealed. Here, we found that end-binding protein 2 (EB2), a MT dynamics regulator, is highly expressed in HCC and predicts poor prognosis of HCC patients. Functional studies show that EB2 overexpression promotes HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…The disruption of microtubule dynamics has been shown to lead to activation of ERK and cell death in earlier studies, such as in hepatocellular carcinoma cell lines, in which end-binding protein 2 was shown to decrease microtubule stability, which then led to ERK activation via activation of Src kinase, part of the focal adhesion complex (Zhong et al 2021). Tien and Chang (2014) demonstrated a link between pERK levels and another member of focal adhesions, RhoA, which stabilises microtubules.…”
Section: Discussionmentioning
confidence: 94%
“…The disruption of microtubule dynamics has been shown to lead to activation of ERK and cell death in earlier studies, such as in hepatocellular carcinoma cell lines, in which end-binding protein 2 was shown to decrease microtubule stability, which then led to ERK activation via activation of Src kinase, part of the focal adhesion complex (Zhong et al 2021). Tien and Chang (2014) demonstrated a link between pERK levels and another member of focal adhesions, RhoA, which stabilises microtubules.…”
Section: Discussionmentioning
confidence: 94%
“…Our results showed that Notch4 silencing downregulated phosphorylation of ERK, JNK, and P38. Meanwhile, Notch4 overexpression increased ERK, JNK, and P38 phosphorylation in A549 and H1299 cells, which was partly abrogated by the specific inhibitors U0126 ( Zhong et al, 2021 ), SP600125 ( Zhang et al, 2021 ), and SB203580 ( Kwak et al, 2021 ). Notably, the increased cell proliferation and migration and inhibited cell apoptosis induced by Notch4 overexpression in A549 and H1299 cells were prevented by the co-administration of U0126, SP600125, or SB203580.…”
Section: Discussionmentioning
confidence: 98%
“…For example, PNO1 mediated the autophagy and apoptosis of liver cancer via this pathway [20]. EB2 also promoted liver cancer proliferation and metastasis via MAPK pathway by regulating microtubule dynamics [21]. Therefore, this pathway might also act as a therapeutic target for liver cancer therapy.…”
Section: Discussionmentioning
confidence: 99%